Remoción de Hierro y Plomo en aguas Residuales por Bioadsorción de la Cáscara de Naranja Agria (Journal on studies and research of academic knowledge, 2016)
This study describes the bioabsorption of bitter orange peel to eliminate iron and lead that are present in effluents. A variation of three physic chemical parameters were used (concentration of metal, size of particles and doses of bio absorbent) assigning two values to each: High and Low. As a result from the variation of parameters, four different experiments were generated for each metal. From the experiments, it was found that for Iron, experiment 3 (pH=4,5, size of particle=0.5mm, concentration of metal=50 mg/L, dose of bio-absorbent =0.5g, time of contact=4h) showed the best percentage for removal (89,65%); whereas, experiment 4 (pH=4,5, size of particle=0.5mm, concentration of metal=30 mg/L, dose of bio-absorbent =0,2g, time of contact=4h) demonstrated a higher absorption capacity (11,08mg of Fe/g of bitter orange peel). The best percentage for the removal of lead was 96,61% and it was obtained in experiment 4 (pH=5, size of particle=0.5mm, concentration of metal=30 mg/L, dose of bio absorbent-0.2g, time of contact=4h), whose capacity for removal was also the best with 14,492 mg of Pb/g of bitter orange peel.
Keywords: Heavy metal; bitter orange peel; bio absorption; removal